Analisis Penerapan SAK EMKM Pada Laporan Keuangan - Iqfiyansyah, Rizal; Nusantoro, Jawoto; Febri Darmayanti, Elmira (Expensive: Jurnal Akuntansi dan Keuangan, 2024)
This research aims to complete the preparation of financial reports carried out by DWI PUTRA UMKM Enterprises and to determine the preparation of DWI PUTRA UMKM financial reports using SAK EMKM. The design that will be used for research is descriptive qualitative research in the form of a case study. The results of the research explain that the preparation of financial reports carried out by PD Dwi Putra is not fully in accordance with the financial accounting standards for micro, small and medium entities (SAK EMKM). The company has not prepared Notes to Financial Reports (CaLK). Based on SAK EMKM, MSME financial reports consist of a minimum profit and loss report, financial position report and notes to financial reports. Meanwhile, according to his confession, PD Dwi Putra's measurements were appropriate except that the presentation of the financial statements was not fully in accordance with the relevant provisions contained in SAK EMKM